2017
DOI: 10.1063/1.4978894
|View full text |Cite
|
Sign up to set email alerts
|

Molecule-specific interactions of diatomic adsorbates at metal-liquid interfaces

Abstract: Ultrafast vibrational dynamics of small molecules on platinum (Pt) layers in water are investigated using 2D attenuated total reflectance IR spectroscopy. Isotope combinations of carbon monoxide and cyanide are used to elucidate inter-adsorbate and substrate-adsorbate interactions. Despite observed cross-peaks in the CO spectra, we conclude that the molecules are not vibrationally coupled. Rather, strong substrate-adsorbate interactions evoke rapid (∼2 ps) vibrational relaxation from the adsorbate into the Pt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 86 publications
1
21
0
Order By: Relevance
“…1c of Ref. 27 ). Such ultra thin metal layers are advantageous for the ultrafast experiments due to their low metal absorption that result in negligible line-shape distortions and reduced scattering.…”
mentioning
confidence: 87%
“…1c of Ref. 27 ). Such ultra thin metal layers are advantageous for the ultrafast experiments due to their low metal absorption that result in negligible line-shape distortions and reduced scattering.…”
mentioning
confidence: 87%
“…[24][25][26] Under these circumstances, immobilization of the sample at the interface allows obtaining surface-sensitive signals from solid-liquid interfaces. With this approach, we have recently investigated the ultrafast vibrational dynamics of surface-bound carbon monoxide 17,27 and cyanide 28 as well as self-assembled organic monolayers under various conditions 18,19,29,30 . Figure 1.…”
mentioning
confidence: 99%
“…In particular, it has been shown that if molecules are immobilized on a surface, relaxation-induced heat generated in the substrate can give rise to cross-peaks between different adsorbate bands. 28,41 Such signals originate from a response (e.g. a frequency-shift and broadening) of the vibrational lineshape of all adsorbate modes on the surface to the substrate temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar method was applied by Mundunkatowa et al [24]. Kraack et al [25,26] demonstrated a surface-enhanced ATR technique, utilizing gold or platinum nanoparticles at the IRE. Aguirre and co-workers [27] presented spectra from the solid-liquid interface in a specially designed microfluidic reactor.…”
Section: Introductionmentioning
confidence: 99%